What is Mental Health Nursing Anyway? Advantages and Issues of Utilizing Duoethnography to Understand Mental Health Nursing - Danda, Michelle (Witness: The Canadian Journal of Critical Nursing Discourse, 2020)
In recent decades scholars have begun to question the value of mental health nursing. The term has lost both conceptual and explanatory power in the modern globalized world in which multidisciplinary teams now carry out many functions once unique to the specialization, yet its distinction persists. The purpose of this paper is to explore an emerging research methodology, duoethnography, as an avenue to revive mental health nursing, by subverting the dominant post-positivist, scientifically driven, medically framed, evidence-based practice perspective, to gain greater understanding of the nuances of mental health nursing practice. Duoethnography offers promise in challenging nursing research norms embedded in an empirically based medical model, however the newness of the method poses potential methodological issues. Duoethnography is a methodology well-suited to explore the question of whether mental health nursing is an outmoded tradition too deeply entrenched in the institutional past, or an emerging profession leading mental health care.